Developing quality indicators for school practice. Issue 1 (2nd January 2019) - Laverdure, Patricia; McCann, Melissa; McLoone, Hannah; Moore, Laura; Reed, Leah
ABSTRACT: Comprehensive measures of the quality of occupational therapy services are critical as the profession as a whole and school-based occupational therapy (SBOT) practitioners in particular examine and strengthen the depth and breadth of the body of knowledge and improve, measure, and advocate for the value of their service to students, families, and schools. Effective measures that illustrate high quality care in a service industry, provide tools to track changes over time, identify areas that need further research, and provide actionable items that lead directly from measurement to professional development planning are largely lacking across the practice specialty. However, effective measurement tools are imperative as the profession reaches toward the American Occupational Therapy Association (AOTA) Vision 2025 (AOTA, 2016 ) and the fulfillment of outcome and accountability requirements of the Individuals with Disabilities Education Improvement Act of 2004 and the Every Student Succeeds Act of 2015. The results of this qualitative study validates a conceptual framework of effective school practice and provides a foundation for the development of technical standards and quality indicators for the practice specialty.